Study on architecture design of electroactive sites on Vanadium Redox Flow Battery (V-RFB) - Suhailah, Sujali; Mohd Rusllim, Mohamed; Oumer, A. N.; Azizan, Ahmad; Leung, P. (2018)
RFB) cell, namely square-, rhombus- and circular-cell designs. The fluid flow of the above-mentioned three electrode design configurations are evaluated under three different cases i.e. no flow (plain) field, parallel flow field and serpentine flow field using numerically designed three-dimensional model in Computational Fluid Dynamics (CFD) software. The cell exhibits different characteristics under different cases, which the circular cell design shows promising results for test-rig development with low pressure drop and better flow distribution of electroactive electrolytes within the cell. Suggestion for further work is highlighted.